Problemas de gênero: resistenências e transgressões das Marias de Rachel de Queiroz - Meyer, Lana Mara Andrade Nóbrega [UNESP] (2015)
This study is a gender investigation composed by the analysis of Guta and Maria Moura (from As três Marias and Memorial de Maria Moura, by Rachel de Queiroz). When analyzing cultural inscriptions and gender impositions, it was our goal to observe how these women react to established patterns of behavior and to the imposed limitations duo to being women. Through Paul Ricoeuer's hermeneutic method we could question the observed contexts and analyze the realities and gender notions found through the concepts defended by Joan Scott and Judith Butler. The proposal of this study was to identify the means by which the resistances of Rachel de Queiros' Marias happen, in a context where being a woman is usually equal to limitation and invisibility. Through the concepts of gender and women's self-being (ser-se mulher), we searched to find the various meanings to the feminine subjectivities present in the analyzed books. We identified that it is through the censorship of their freedom that these women create the means for their transgressions and resistances. Marriage, religion, sexuality and power are some of the aspects here studied, once they are part of the context that structure women's domination. Both characters present behaviors of outbreak of social norms, using their own struggles to experience things that wouldn't be possible otherwise. These women, by escaping the given and imposed definition of woman, and creating their own, reveal the mechanisms behind gender imposition and create a sense of freedom never before experienced